Comercialización del arroz paddy en la zona de Babahoyo - Sánchez Mayorga, Maycol Agustín (2019)
The purpose of this document as a practical component is to inquire about the commercialization of paddy rice in the Babahoyo area, which especially affects small and medium-sized rice producers, due to the high production cost of producing this product to obtain high yields, which in the end is economically affected when commercialized. In Ecuador, specifically in the province of Los Ríos in the Babahoyo area, the main problem that has an impact on paddy rice production is its commercialization, which has led farmers to obtain large economic losses when trying to sell their products, which is linked to the high production costs generated by this crop. The execution of this document was carried out with the analysis of texts, books, magazines, newspapers, congresses, presentations, scientific articles and review of web pages. All the information was reviewed continuously and previously complementary readings were made with books related to other areas such as cemercio and business administration. The research was submitted to the analysis, synthesis and summary technique where everything related to the marketing of paddy rice in the Babahoyo area was developed. Based on the above, it was determined that in the Province of Los Ríos, specifically in the Babahoyo area, there is a gap between the costs for rice crop production and the marketing of this grass; there is no control in the referential price proposed by government agencies for the sale of paddy rice; The inclusion of intermediaries has an impact on the economic gain of small and medium-sized farmers and consumer prices are related to per capita consumption with the same tendency in the external market.